Holmas miljonprogram kan självförvaltning bidra till biofilisk design - Corshammar,Amelia; Malm,Lina (2026)
This study examines how people’s well-being in residential areas is affected by the outdoor environments and biophilic design. We have chosen to focus specifically on Holma in Malmö, an area built during the million homes programme era. The aim of the study is to analyze how Holma’s residential environment relates to biophilic design, both in present time and in connection with renovations and planned future urban transformation. To carry out this work, we conducted literature studies, site visits and interviews with representatives from MKB, the municipal housing company in Malmö which provides rental housing. Based on the results of our study, we can see that Holma has evolved from a functionalist residential area to one with more biophilic elements, such as self-management, green corridors and spaces, and artistic decoration. The conclusion indicates that self-management contributes to several biophilic aspects. Particularly significant for Holma are place-based relationships and developed human-nature connections, as self- management fosters a sense of protection and pride among residents, stemming from their participation in decision making and their ability to influence the residential environment.
Keywords: Biofilisk design; Bostadsmiljö; Holma; Miljonprogrammet; Utomhusmiljö. Biophilic design; Residental environment; the Million Homes Programme; Outdoor environment.